Cutter with high-toughness antirust coating and preparation method thereof

By forming amorphous nanocarbide layer rich in sp2 carbon on the ATS-34 stainless steel tool and carrying out surface laser impact strengthening and rare earth nickel boron and nitrogen co-permeation treatment, the insufficient performance of the tool in high temperature or strong corrosion environment is solved. , significantly improves hardness and toughness, extends service life and reduces the risk of cracking.

CN119121180AInactive Publication Date: 2024-12-13NINGBO XINGWEI CUTTING TOOLS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411586927.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The cutting performance of ATS-34 stainless steel tools in high temperature or strong corrosion environments has deteriorated, and their corrosion resistance and toughness are insufficient, resulting in the problem of screing or fractures that are prone to high load, high-speed cutting or harsh environments.

Method used

Chemical deposition method is used to form an amorphous nanocarbide layer rich in sp2 carbon on the tool substrate, and combined with surface laser impact enhancement, rare earth nickel-boron-nitrogen co-permeation and titanium permeation treatment, to form an alternatingly grown composite coating to enhance The hardness, toughness and impact resistance of the tool reduce crack generation and expansion.

Benefits of technology

It significantly improves the hardness, wear resistance and impact resistance of the tool, extends the service life, reduces the risk of cracking and fracture, and meets the high performance requirements under harsh working conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a cutter with a high-toughness antirust coating. The preparation method comprises the following steps: S1, providing pretreated ATS-34 stainless steel as a cutter base material; s2, a layer of amorphous nanometer carbide layer rich in sp2 carbon is chemically deposited; s3, after primary surface laser shock peening treatment is carried out, rare earth nickel boron nitrogen primary co-permeation treatment and primary aging treatment operation are carried out; s4, operation of the step S2 and the step S3 is repeatedly conducted, the alternately-growing composite coating is obtained, and the thickness of the nanometer carbide layer obtained after chemical deposition is controlled to be decreased and changed in a gradient mode; s5, the tool base material is placed in mechanical energy permeation assisting equipment containing a titanizing agent to be subjected to titanizing treatment; and performing heat treatment to obtain the cutter with the high-toughness anti-rust coating. The prepared cutter has high hardness, high toughness, rust resistance and the like, and can meet the long-term durable use requirement under harsh conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cutting tools, and in particular to a cutting tool with a high-toughness anti-rust coating and a preparation method thereof. Background Art

[0002] In modern manufacturing, especially in the field of high-precision machining, the performance requirements for tool materials are getting higher and higher. As a commonly used tool material, ATS-34 stainless steel has certain hardness and wear resistance, but it still faces some challenges in practical applications. The cutting performance of ATS-34 steel decreases under high temperature or strong corrosive environment, and its corrosion resistance and toughness cannot fully meet the harsh processing conditions. For example, in the process of high-speed cutting, ATS-34 steel tools may be quickly damaged by thermal wear and chemical wear, and in a humid or corrosive environment, its surface is prone to rust, resulting in a shortened tool life. In addition, the insufficient toughness of ATS-34 steel may also cause the tool to easily break or break when subjected to severe impact, which is particularly obvious when machining hard materials. Therefore, although ATS-34 steel meets the basic performance requirements of tools to a certain extent, its insufficient performance under high load, high-speed cutting or harsh machining environments limits its application in the field of high-end manufacturing. At present, the manufacturing industry has higher and higher requirements for the comprehensive performance of tool materials, and it is urgent to develop a new type of tool material or improve the performance of existing materials to meet more demanding processing requirements. Summary of the invention

[0003] In view of the above shortcomings of the prior art, the present invention, on the one hand, provides a method for preparing a cutting tool with a high-toughness anti-rust coating, so as to solve the problem that the existing cutting tools cannot have both high hardness, high toughness and rust resistance, and the cutting tools are prone to chipping and breakage under high load, high-speed cutting or harsh processing environments.

[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a cutting tool with a high-toughness anti-rust coating, the method comprising the following steps: S1: Provide pre-treated ATS-34 stainless steel as tool substrate; S2: chemically depositing a layer of amorphous nanocarbide rich in sp2 carbon on the tool substrate obtained in step S1; the present invention chemically deposits a layer of amorphous nanocarbide rich in sp2 carbon on the tool substrate. On the one hand, the hardness and wear resistance of the tool surface are significantly improved, because the amorphous nanocarbide layer itself has extremely high hardness and good wear resistance, and can effectively resist wear and tear during the cutting process, thereby extending the service life of the tool; on the other hand, the impact resistance and toughness of the tool substrate are enhanced. Due to the uniformity and continuity of the amorphous structure, the tool can better absorb and disperse stress when subjected to severe impact and pressure changes, reduce the generation and expansion of cracks, thereby improving the reliability and stability of the tool under complex processing conditions.

[0005] S3: After subjecting the tool substrate obtained in step S2 to a surface laser shock intensive treatment, a rare earth nickel boron nitrogen co-diffusion treatment and an aging treatment are performed; further, the present invention not only forms a stress-induced dense layer on the tool surface through a surface laser shock intensive treatment combined with a rare earth nickel boron nitrogen co-diffusion treatment and an aging treatment, thereby improving the hardness and wear resistance of the tool surface, enabling the tool to withstand greater cutting forces and more complex cutting conditions during the cutting process, reducing tool wear and extending tool life; and, through the introduction of rare earth elements and aging treatment, optimizes the microstructure of the tool material, enhances the toughness and impact resistance of the material, and enables the tool to better resist the generation and spread of cracks when subjected to drastic temperature and pressure changes, thereby significantly improving the reliability and durability of the tool, and meeting the high requirements for tool performance under harsh working conditions.

[0006] S4: Repeat the operations of step S2 and step S3 to obtain an alternately grown composite coating, and control the thickness of the nanocarbide layer after chemical deposition to decrease in a gradient; the tool prepared by step S4 of the present invention shows that the coating has a gradient functional structure, which not only forms a carbide protective layer with high hardness and high wear resistance on the surface of the tool to effectively resist wear and tear during cutting, but also forms a gentle stress transition zone between the coating and the substrate, reducing the risk of coating peeling and tool breakage caused by stress concentration. At the same time, the gradient-changing nanocarbide layer also provides the tool with good impact resistance and fracture toughness, ensuring that the tool is not prone to chipping or breaking when subjected to severe impact and pressure changes, significantly improving the service life and reliability of the tool, and meeting the high requirements for tool performance under harsh working conditions.

[0007] S5: Place the tool substrate obtained in step S4 in a mechanical energy-assisted infiltration device equipped with a titanium infiltration agent for titanium infiltration treatment; after heat treatment, a tool with a high-toughness anti-rust coating is obtained. The present application further uses mechanical energy to assist infiltration to reduce the diffusion time, lower the processing temperature, and reduce the performance impact on the substrate structure, which is beneficial to improving product quality. The present application uses the protection of a composite coating to ensure that the tool has high toughness and is rust-resistant while not prone to problems such as chipping.

[0008] As a preferred technical solution, the pretreatment step is: placing the tool substrate in a solution composed of 3-6wt% sodium hydroxide and 5-8wt% sodium carbonate for ultrasonic degreasing for 5-10 minutes, then placing it in a 1-5wt% hydrochloric acid solution for ultrasonic rust removal for 5-10 minutes, and finally rinsing with anhydrous ethanol and blowing dry.

[0009] As a preferred technical solution, the nanocarbide layer is at least one of nanodiamond, nanosilicon carbide, nanotantalum carbide, and nanotitanium carbide.

[0010] As a preferred technical solution, the surface laser shock strengthening treatment is set with a laser power of 1 to 2 kilowatts, a pulse width of 10 to 20 nanoseconds, a frequency of 5 to 10 hertz, and an operation time of 10 to 30 seconds.

[0011] As a preferred technical solution, the steps of the rare earth nickel boron nitrogen single co-diffusion treatment are: placing the tool substrate in a pressure vessel filled with a rare earth nickel boron co-diffusion agent, heating the rare earth nickel boron co-diffusion agent so that the rare earth nickel boron co-diffusion agent is in a boiling state, introducing nitrogen-containing gas into the pressure vessel and performing gas discharge, keeping the temperature at 600-650°C for 2-3 hours and then stopping the discharge, increasing the pressure of the pressure vessel to 0.1-0.3MPa, and obtaining the tool substrate after the rare earth nickel boron nitrogen single co-diffusion.

[0012] As a preferred technical solution, the operating temperature of the primary aging treatment is 300-500° C., and the time is 1-5 hours.

[0013] As a preferred technical solution, in step S4, step S2 and step S3 are repeated at least twice; and each time the operation is repeated, the thickness of the subsequent nanocarbide layer is controlled to be 70-90% of the thickness of the previous nanocarbide layer.

[0014] As a preferred technical solution, the titanium infiltration treatment is carried out under the conditions of a mechanical energy-assisted infiltration equipment roller speed of 50 to 100 r / min and a heating rate of 5.5 to 8.5°C / min, heating from room temperature to 400 to 420°C, then keeping warm for 4 to 6 hours, and then cooling to room temperature with the furnace to complete the operation.

[0015] As a preferred technical solution, in step S5, the heat treatment operation includes quenching and tempering treatment, and the operating temperature of the tempering treatment is 200-250° C. and the time is 60-90 min.

[0016] Another aspect of the present invention is to provide a cutting tool having a high-toughness anti-rust coating, wherein the cutting tool is prepared by the preparation method as described above.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing a cutting tool with a high-toughness anti-rust coating in the present application solves the problem that existing cutting tools cannot have both high hardness, high toughness and rust resistance, and that the cutting tools are prone to chipping and breakage under high load, high-speed cutting or harsh processing environments, and can meet the requirements of long-term use under harsh conditions. DETAILED DESCRIPTION

[0018] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0019] Example 1 The method for preparing a cutting tool having a high-toughness anti-rust coating in this embodiment comprises the following steps: Step S1: ATS-34 stainless steel after pretreatment is provided as a tool substrate; the chemical composition and weight percentage of the ATS-34 stainless steel are as follows: C is 1.05, Si is 0.35, Mn is 0.4, P is 0.03, S is 0.02, Mo is 4, Cr is 14, and the rest is Fe and unavoidable impurities. The pretreatment step is: the tool substrate is placed in a solution of 6wt% sodium hydroxide and 8wt% sodium carbonate for ultrasonic degreasing for 10 minutes, then placed in a 5wt% hydrochloric acid solution for ultrasonic rust removal for 10 minutes, and finally rinsed with anhydrous ethanol and blown dry.

[0020] Step S2: On the tool substrate obtained in step S1, a layer of amorphous nano-carbide rich in sp2 carbon is chemically deposited; the chemical deposition is carried out by chemical vapor deposition (CVD) method, wherein the deposition pressure is 2.5 kPa, the substrate temperature is 820 ° C, the atmosphere is 3% CH4-a small amount of H2-Ar, and the atmosphere gas flow rate is controlled to be 150 cm 3 / min, the deposition time is 2h, and the thickness of the amorphous nanodiamond carbide layer is 120nm.

[0021] Step S3: After the tool substrate obtained in step S2 is subjected to a surface laser shock intensive treatment, a rare earth nickel boron nitrogen co-penetration treatment and an aging treatment are performed; the surface laser shock intensive treatment is set to have a laser power of 2 kilowatts, a pulse width of 10 nanoseconds, a frequency of 5 hertz, and an operation time of 10 seconds; the rare earth nickel boron nitrogen co-penetration treatment comprises the following steps: placing the tool substrate in a pressure vessel containing a rare earth nickel boron co-penetration agent, heating the rare earth nickel boron co-penetration agent to make the rare earth nickel boron co-penetration agent in a boiling state, introducing nitrogen-containing gas into the pressure vessel and performing gas discharge, stopping the discharge after keeping the temperature at 600°C for 3 hours, and increasing the pressure of the pressure vessel to 0.3 MPa to obtain the tool substrate after a rare earth nickel boron nitrogen co-penetration. The rare earth nickel boron co-penetration agent is prepared from 5% B4C (boron carbide), 5% KBF4 (potassium fluoroborate), 5% C (activated carbon), 2% CeO2 (cerium oxide), 1.4% La2O3 (lanthanum oxide) and 5% NiCl2 (nickel chloride). The nitrogen-containing gas is a combination of nitrogen and argon in a volume ratio of 2:1. The gas discharge is performed in a glow discharge manner. The operating temperature of the primary aging treatment is 500° C. and the time is 2 hours.

[0022] Step S4: Repeat step S2 and step S3 for 3 times to obtain an alternately grown composite coating, and control the thickness of the nanocarbide layer after chemical deposition to decrease in a gradient; each time the operation is repeated, the thickness of the subsequent nanocarbide layer is controlled to be 80% of the thickness of the previous nanocarbide layer.

[0023] Step S5: Place the tool substrate obtained in step S4 in a mechanical energy-assisted infiltration device equipped with a titanium infiltration agent for titanium infiltration treatment; after heat treatment, a tool with a high-toughness anti-rust coating is obtained. The titanium infiltration treatment is carried out under the conditions of a roller speed of 100 r / min and a heating rate of 5.5℃ / min in the mechanical energy-assisted infiltration device, from room temperature to 400℃, and then kept warm for 6 hours, and then cooled to room temperature with the furnace to complete the operation; the titanium infiltration agent is composed of titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride, and the mass ratio of the titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride is 55:45:1:5. The heat treatment operation includes quenching and tempering treatment. The quenching medium of the quenching is water, the quenching temperature is 380℃, and the quenching time is 120min; the tool substrate is heated to 860℃ before quenching. The operating temperature of the tempering treatment is 250℃ and the time is 90min.

[0024] The tool samples of this embodiment showed no cracking after appearance inspection; the microhardness reached 2180HV; the impact toughness of the tool was 33 times that of untreated ATS-34 stainless steel, and the corrosion resistance was 85 times that of untreated ATS-34 stainless steel.

[0025] Example 2 The method for preparing a cutting tool having a high-toughness anti-rust coating in this embodiment comprises the following steps: Step S1: ATS-34 stainless steel after pretreatment is provided as a tool substrate; the chemical composition and weight percentage of the ATS-34 stainless steel are as follows: C is 1.05, Si is 0.35, Mn is 0.4, P is 0.03, S is 0.02, Mo is 4, Cr is 14, and the rest is Fe and unavoidable impurities. The pretreatment step is: placing the tool substrate in a solution of 5wt% sodium hydroxide and 6wt% sodium carbonate for ultrasonic degreasing for 8 minutes, then placing it in a 3wt% hydrochloric acid solution for ultrasonic rust removal for 8 minutes, and finally rinsing with anhydrous ethanol and blowing dry.

[0026] Step S2: On the tool substrate obtained in step S1, a layer of amorphous nano-carbide rich in sp2 carbon is chemically deposited; the chemical deposition is carried out by chemical vapor deposition (CVD) method, wherein the deposition pressure is 2 kPa, the substrate temperature is 850 ° C, the atmosphere is 2.5% CH4-a small amount of H2-Ar, and the atmosphere gas flow rate is controlled to be 120 cm 3 / min, the deposition time is 4h, and the thickness of the amorphous nanodiamond carbide layer is 100nm.

[0027] Step S3: After the tool substrate obtained in step S2 is subjected to a surface laser shock peening treatment, it is subjected to a rare earth nickel boron nitrogen co-diffusion treatment and an aging treatment operation; the surface laser shock peening treatment sets its laser power to 1.5 kilowatts, a pulse width to 15 nanoseconds, a frequency to 7 hertz, and an operation time to 20 seconds; the steps of the rare earth nickel boron nitrogen co-diffusion treatment are: placing the tool substrate in a pressure vessel filled with a rare earth nickel boron co-diffusion agent, heating the rare earth nickel boron co-diffusion agent to a boiling state, introducing nitrogen-containing gas into the pressure vessel and performing gas discharge, stopping the discharge after keeping warm at 620°C for 3 hours, and increasing the pressure of the pressure vessel to 0.2 MPa to obtain the tool substrate after the rare earth nickel boron nitrogen co-diffusion. The rare earth nickel-boron co-diffusion agent is prepared from 6% B4C (boron carbide), 4% KBF4 (potassium fluoroborate), 5% C (activated carbon), 3% CeO2 (cerium oxide), 1.6% La2O3 (lanthanum oxide) and 8% NiCl2 (nickel chloride). The nitrogen-containing gas is a combination of nitrogen and argon in a volume ratio of 2:1. The gas discharge is carried out in a glow discharge manner. The operating temperature of the primary aging treatment is 450°C and the time is 3 hours.

[0028] Step S4: Repeat step S2 and step S3 for 3 times to obtain an alternately grown composite coating, and control the thickness of the nanocarbide layer after chemical deposition to decrease in a gradient; each time the operation is repeated, the thickness of the subsequent nanocarbide layer is controlled to be 85% of the thickness of the previous nanocarbide layer.

[0029] Step S5: Place the tool substrate obtained in step S4 in a mechanical energy-assisted infiltration device equipped with a titanium infiltration agent for titanium infiltration treatment; after heat treatment, a tool with a high-toughness anti-rust coating is obtained. The titanium infiltration treatment is carried out under the conditions of a roller speed of 100 r / min and a heating rate of 6.5℃ / min in the mechanical energy-assisted infiltration device, from room temperature to 410℃, and then kept warm for 5 hours, and then cooled to room temperature with the furnace to complete the operation; the titanium infiltration agent is composed of titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride, and the mass ratio of the titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride is 60:40:2:4. The heat treatment operation includes quenching and tempering treatment. The quenching medium of the quenching is water, the quenching temperature is 380℃, and the quenching time is 120min; the tool substrate is heated to 860℃ before quenching. The operating temperature of the tempering treatment is 250℃ and the time is 90min.

[0030] The tool samples of this embodiment showed no cracking after appearance inspection; the microhardness reached 2210HV; the impact toughness of the tool was 27 times that of untreated ATS-34 stainless steel, and the corrosion resistance was 81 times that of untreated ATS-34 stainless steel.

[0031] Example 3 The method for preparing a cutting tool having a high-toughness anti-rust coating in this embodiment comprises the following steps: Step S1: ATS-34 stainless steel after pretreatment is provided as a tool substrate; the chemical composition and weight percentage of the ATS-34 stainless steel are as follows: C is 1.05, Si is 0.35, Mn is 0.4, P is 0.03, S is 0.02, Mo is 4, Cr is 14, and the rest is Fe and unavoidable impurities. The tool substrate is placed in a solution of 6wt% sodium hydroxide and 8wt% sodium carbonate for ultrasonic degreasing for 10 minutes, then placed in a 5wt% hydrochloric acid solution for ultrasonic rust removal for 10 minutes, and finally rinsed with anhydrous ethanol and blown dry.

[0032] Step S2: On the tool substrate obtained in step S1, a layer of amorphous nano-carbide rich in sp2 carbon is chemically deposited; the chemical deposition is carried out by chemical vapor deposition (CVD) method, wherein the deposition pressure is 1.5 kPa, the substrate temperature is 880 ° C, the atmosphere is 2% CH4-a small amount of H2-Ar, and the atmosphere gas flow rate is controlled to be 100 cm 3 / min, the deposition time is 6h, and the thickness of the amorphous nano-diamond carbide layer is 80nm.

[0033] Step S3: After the tool substrate obtained in step S2 is subjected to a surface laser shock peening treatment, it is subjected to a rare earth nickel boron nitrogen co-penetration treatment and an aging treatment operation; the surface laser shock peening treatment sets its laser power to 1 kilowatt, pulse width to 20 nanoseconds, frequency to 5 hertz, and operation time to 30 seconds; the steps of the rare earth nickel boron nitrogen co-penetration treatment are: placing the tool substrate in a pressure vessel filled with a rare earth nickel boron co-penetration agent, heating the rare earth nickel boron co-penetration agent to a boiling state, introducing nitrogen-containing gas into the pressure vessel and performing gas discharge, stopping the discharge after keeping warm at 650°C for 2 hours, and increasing the pressure of the pressure vessel to 0.15 MPa to obtain the tool substrate after the rare earth nickel boron nitrogen co-penetration. The rare earth nickel-boron co-diffusion agent is prepared from 7% B4C (boron carbide), 3% KBF4 (potassium fluoroborate), 5% C (activated carbon), 3% CeO2 (cerium oxide), 1.8% La2O3 (lanthanum oxide) and 10% NiCl2 (nickel chloride). The nitrogen-containing gas is a combination of nitrogen and argon in a volume ratio of 2:1. The gas discharge is carried out in a glow discharge manner. The operating temperature of the primary aging treatment is 400°C and the time is 3 hours.

[0034] Step S4: Repeat step S2 and step S3 for 3 times to obtain an alternately grown composite coating, and control the thickness of the nanocarbide layer after chemical deposition to decrease in a gradient; each time the operation is repeated, the thickness of the subsequent nanocarbide layer is controlled to be 90% of the thickness of the previous nanocarbide layer.

[0035] Step S5: Place the tool substrate obtained in step S4 in a mechanical energy-assisted infiltration device equipped with a titanium infiltration agent for titanium infiltration treatment; after heat treatment, a tool with a high-toughness anti-rust coating is obtained. The titanium infiltration treatment is carried out under the conditions of a roller speed of 100 r / min and a heating rate of 8.5℃ / min in the mechanical energy-assisted infiltration device, from room temperature to 420℃, and then kept warm for 4 hours, and then cooled to room temperature with the furnace to complete the operation; the titanium infiltration agent is composed of titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride, and the mass ratio of the titanium powder, aluminum oxide, ammonium chloride and lanthanum chloride is 65:35:3:3. The heat treatment operation includes quenching and tempering treatment. The quenching medium of the quenching is water, the quenching temperature is 380℃, and the quenching time is 120min; the tool substrate is heated to 860℃ before quenching. The operating temperature of the tempering treatment is 250℃ and the time is 90min.

[0036] The tool samples of this embodiment showed no cracking after appearance inspection; the microhardness reached 2080HV; the impact toughness of the tool was 31 times that of untreated ATS-34 stainless steel, and the corrosion resistance was 83 times that of untreated ATS-34 stainless steel.

[0037] Comparative Example 1 The operation steps of the preparation method of the tool in this comparative example are basically the same as those of Example 1, except that step S2 is omitted in the preparation method of this comparative example.

[0038] 20 cutting tool samples of this embodiment were inspected for cracks; the microhardness reached 2210HV; the impact toughness of the cutting tool was twice that of untreated ATS-34 stainless steel, and the corrosion resistance was 84 times that of untreated ATS-34 stainless steel.

[0039] Comparative Example 2 The operation steps of the preparation method of the tool in this comparative example are basically the same as those of Example 1, except that step S3 is omitted in the preparation method of this comparative example.

[0040] The 20 cutting tool samples of this embodiment showed no cracking after appearance inspection; the microhardness reached 1580HV; the impact toughness of the cutting tool was 28 times that of untreated ATS-34 stainless steel, and the corrosion resistance was 78 times that of untreated ATS-34 stainless steel.

[0041] Comparative Example 3 The operation steps of the preparation method of the tool in this comparative example are basically the same as those of Example 1, except that step S4 is omitted in the preparation method of this comparative example.

[0042] After appearance inspection, 20 cutting tool samples of this embodiment showed 1 crack; the microhardness reached 1670HV; the impact toughness of the cutting tool was 10 times that of untreated ATS-34 stainless steel, and the corrosion resistance was 74 times that of untreated ATS-34 stainless steel.

[0043] It can be seen that the patent of the present invention has considerable advantages over the currently used technology. The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may have various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a cutting tool having a high-toughness anti-rust coating, characterized in that: The preparation method comprises the following steps: S1: Provide pre-treated ATS-34 stainless steel as tool substrate; S2: chemically depositing a layer of amorphous nano-carbide rich in sp2 carbon on the tool substrate obtained in step S1; S3: subjecting the tool substrate obtained in step S2 to a surface laser shock peening treatment, and then to a rare earth nickel boron nitrogen co-diffusion treatment and an aging treatment operation; S4: Repeating the operations of step S2 and step S3 to obtain an alternately grown composite coating, and controlling the thickness of the nanocarbide layer after chemical deposition to decrease in a gradient; S5: placing the tool substrate obtained in step S4 in a mechanical energy-assisted titanium infiltration device containing a titanium infiltration agent for titanium infiltration treatment; after heat treatment, a tool having a high-toughness anti-rust coating is obtained.

2. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The pretreatment step is: placing the tool substrate in a solution of 3-6wt% sodium hydroxide and 5-8wt% sodium carbonate for ultrasonic degreasing for 5-10 minutes, then placing it in a 1-5wt% hydrochloric acid solution for ultrasonic rust removal for 5-10 minutes, and finally rinsing with anhydrous ethanol and drying.

3. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The nano carbide layer is at least one of nano diamond, nano silicon carbide, nano tantalum carbide and nano titanium carbide.

4. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The surface laser shock strengthening treatment is set to have a laser power of 1 to 2 kilowatts, a pulse width of 10 to 20 nanoseconds, a frequency of 5 to 10 hertz, and an operation time of 10 to 30 seconds.

5. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The steps of the rare earth nickel boron nitrogen single co-diffusion treatment are: placing a tool substrate in a pressure vessel filled with a rare earth nickel boron co-diffusion agent, heating the rare earth nickel boron co-diffusion agent to make it boil, introducing nitrogen-containing gas into the pressure vessel and performing gas discharge, keeping the temperature at 600-650° C. for 2-3 hours and then stopping the discharge, increasing the pressure of the pressure vessel to 0.1-0.3 MPa, and obtaining the tool substrate after the rare earth nickel boron nitrogen single co-diffusion.

6. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The operating temperature of the primary aging treatment is 300-500° C., and the time is 1-5 hours.

7. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: In step S4, the operations of step S2 and step S3 are repeated at least twice; and each time the operation is repeated, the thickness of the subsequent nanocarbide layer is controlled to be 70-90% of the thickness of the previous nanocarbide layer.

8. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: The titanium infiltration treatment is carried out under the conditions of a mechanical energy-assisted infiltration equipment roller speed of 50-100 r / min and a heating rate of 5.5-8.5°C / min, heating from room temperature to 400-420°C, then keeping the temperature for 4-6 hours, and then cooling to room temperature with the furnace to complete the operation.

9. The method for preparing a cutting tool having a high-toughness anti-rust coating as claimed in claim 1, characterized in that: In step S5, the heat treatment operation includes quenching and tempering treatment, and the operating temperature of the tempering treatment is 200-250° C. and the time is 60-90 minutes.

10. A cutting tool with a high-toughness anti-rust coating, characterized in that: The cutting tool is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fused salt system for molybdenum or molybdenum alloy binary co-penetration, composite catalyst and application

    CN105385989A

  • Co-permeation technology for multi-element alloy co-permeated anticorrosive layer on surface of steel product

    CN107916394A

  • Nickel-boron-nitrogen co-doped diamond electrode as well as preparation thereof and application thereof

    CN107988616A

  • Gradient ceramic nickel multilayer film and chemical heat treatment preparation method thereof

    CN113621921A

  • Safety knife blade with high-hardness anti-rust coating and preparation method

    CN116121694A